In situ local shock speed and transit shock speed - S. Watari; T. Detman (Annales Geophysicae, 1998)
A useful index for estimating the transit speeds was derived by analyzing interplanetary shock observations. This index is the ratio of the in situ local shock speed and the transit speed; it is 0.6–0.9 for most observed shocks. The local shock speed and the transit speed calculated for the results of the magnetohydrodynamic simulation show good agreement with the observations. The relation expressed by the index is well explained by a simplified propagation model assuming a blast wave. For several shocks the ratio is approximately 1.2, implying that these shocks accelerated during propagation in slow-speed solar wind. This ratio is similar to that for the background solar wind acceleration. Keywords. Interplanetary physics (Flare and stream dynamics; Interplanetary shocks; Solar wind plasma)